IMPROVING THE ACCOUNT OF GOODS MATERIAL RESERVES IN BUDGET ORGANIZATIONS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This theme emphasizes the critical need for enhanced management and accounting practices regarding material reserves within budget organizations. Material reserves, encompassing inventory, supplies, and raw materials, are essential for the efficient functioning of public sector services. Traditional accounting methods pose challenges such as inadequate reporting systems, lack of standardization, human error, and limited staff training, leading to discrepancies in inventory management. To address these issues, the theme suggests implementing integrated management systems, standardizing accounting processes, investing in training for staff, and adopting advanced technologies such as RFID and cloud-based solutions. The aim is to achieve greater accuracy, efficiency, and transparency in managing goods and material reserves. By improving these practices, budget organizations can ensure better resource allocation, minimize wastage, and enhance overall public trust in financial stewardship. This multifaceted approach provides a roadmap for organizations seeking to optimize their inventory management and support effective public service delivery.